RATING SCALE FOR QUALITY OF SERVICES PROVIDED BY gyms (QUASPg) - Vinicius Almeida Calesco; Jorge Both (Journal of Physical Education)
ABSTRACT In order to identify factors that interfere with gym clients’ choice, permanence and withdrawal, the aim of this study was to build and validate an instrument to assess the quality of services provided by gyms. The study has four stages (question identification, evaluation of the analysis matrix clarity, importance and relevance, reliability analysis on instrument questions, and question analysis as to the instrument construct). A total of 51 criteria were identified and deemed important for service quality. The Analysis Matrix was composed of the following dimensions: structure, management, marketing and accessibility. The question and matrix evaluation ruled out 19 questions. The reliability evaluation excluded one question and the accessibility dimension. The Confirmatory Factor Analysis model evidenced adequate goodness of fit after the exclusion of eight questions and performance of six correlations. Composite Reliability, Average Variance Extracted, Discriminant Validity, and Cronbach’s alpha showed acceptable values. Thus, it is concluded that the instrument called “Rating Scale for Quality of Services Provided by Gyms” (QUASPG) has satisfactory psychometric properties, being composed of 21 questions distributed into three dimensions, namely: Environment, Management and Marketing.